Manufacturing Or Development Of A Performance Management System (Hr) At My Indothai Spa & Massage - Renita Millena; Muhammad Donal Mon (ConCEPt - Conference on Community Engagement Project, 2023)
My Indothai Spa & Massage was formed in 1999 by Gideon Septianto Hidayat, the owner. My Indothai Spa & Massage is domiciled at Komp Penuin Center Blok K No 2-3-4, Batu Selicin, Kec. Lubuk Baja, Batam City. This business is engaged in services, which offers various types of massage and spa services for body relaxation. The purpose of this practical work is to assist MSMEs in preparing and forming forms for employees. The scope of this project is to design or develop a performance management system (HR) at My Indothai Spa & Massage as a source of information, recording and assessment of human resources. Data collection techniques used are interviews and observation. The result is the creation of organizational structures, attendance forms, leave forms, permit forms, training & development forms, attendance forms, performance appraisal forms, skills matrix and forms for filling in data regarding human resources using MS Excel.